2003
DOI: 10.1128/aac.47.3.948-955.2003
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Approach to Understanding Antibiotic Action

Abstract: We have used proteomic technology to elucidate the complex cellular responses of Bacillus subtilis to antimicrobial compounds belonging to classical and emerging antibiotic classes. We established on twodimensional gels a comprehensive database of cytoplasmic proteins with pIs covering a range of 4 to 7 that were synthesized during treatment with antibiotics or agents known to cause generalized cell damage. Although each antibiotic showed an individual protein expression profile, overlaps in the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
269
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(275 citation statements)
references
References 35 publications
1
269
3
2
Order By: Relevance
“…Today, the infectious diseases have become worldwide a leading cause of death, therefore, their study has become a global concern [40]. The emergence of multidrugresistance in the pathogens is threatening the clinical efficiency of many existing antibiotics [41]. It is a matter of fact that a number of infectious diseases have been treated with herbal medicines throughout the history of mankind.…”
Section: History Of Medicinal Plantsmentioning
confidence: 99%
“…Today, the infectious diseases have become worldwide a leading cause of death, therefore, their study has become a global concern [40]. The emergence of multidrugresistance in the pathogens is threatening the clinical efficiency of many existing antibiotics [41]. It is a matter of fact that a number of infectious diseases have been treated with herbal medicines throughout the history of mankind.…”
Section: History Of Medicinal Plantsmentioning
confidence: 99%
“…The clinical efficacy of many existing antibiotics is being threatened by the emergence of multidrug-resistant pathogens (Bandow et al, 2003). Plant products, either as pure compounds or as standardized extracts, provide promising opportunities for new anti-infective drugs.…”
Section: Various Pathogenic Bacteria Including Escherichia Coli Andmentioning
confidence: 99%
“…The barks of different species of Juglans regia have been chemically analyzed in numerous studies. Major components in obtained essential oils of Juglans regia include phenolic compounds, terpenoids, alkaloids, flavonoids and steroids (17). It is reported that the bark of Juglans regia Li.…”
Section: Introductionmentioning
confidence: 99%